1997
DOI: 10.1095/biolreprod57.5.1104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Equine Glycoprotein Hormone Alpha-Subunit Gene Reveals Divergence in the Mechanism of Pituitary and Placental Expression1

Abstract: The equine glycoprotein hormone alpha-subunit gene is expressed in both pituitary and placenta, unlike that of all other nonprimate mammals studied, in which expression is limited to pituitary. Previous studies of the 5'-flanking region of the equine alpha-subunit promoter have revealed unique characteristics as well as similarities with the human alpha-subunit promoter, which demonstrates a similar pattern of tissue-specific expression. We have cloned and sequenced the equine alpha-subunit gene and have used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Steger and co-workers reported that an -activating element located within proximal 5 flanking region of eCG subunit promoter was responsible for PKA induction when evaluated in the JEG-3 human choriocarcinoma cell line (Steger et al 1991). In contrast, Farmerie and co-workers reported that activation of the PKA pathway did not stimulate activity of the eCG subunit promoter in the BeWo human choriocarcinoma cell line (Farmerie et al 1997). Nonetheless, our data strongly suggest that the PKA pathway regulates expression of the endogenous eCG subunit gene in our clonal cell lines.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Steger and co-workers reported that an -activating element located within proximal 5 flanking region of eCG subunit promoter was responsible for PKA induction when evaluated in the JEG-3 human choriocarcinoma cell line (Steger et al 1991). In contrast, Farmerie and co-workers reported that activation of the PKA pathway did not stimulate activity of the eCG subunit promoter in the BeWo human choriocarcinoma cell line (Farmerie et al 1997). Nonetheless, our data strongly suggest that the PKA pathway regulates expression of the endogenous eCG subunit gene in our clonal cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data indicate that GCMa is not expressed in the equine clonal cell lines or endometrial cups and, therefore, presumably does not play a role in initiating expression of the eCG subunit gene. The 5 flanking region of eCG subunit promoter harbors a consensus nuclear receptor half-site (AGGTCA) (Farmerie et al 1997), and so far, two orphan nuclear receptors (ERR and ) have been shown to be expressed in the placenta and are essential for placental development (Luo et al 1997, Heard et al 2000. ERR expression is restricted to the chorion during embryogenesis and to a limited number of adult tissues (Pettersson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example several nonmouse gene promoters that have been introduced into transgenic mice which have not been able to direct appropriate expression of marker genes to the areas expected. These promoter elements include those of the human glucagon gene (Nian et al, 1999), the equine glycoprotein hormone ␣-subunit gene (Farmerie et al, 1997), the human and chick type X-collagen gene (Beier et al, 1996), and a lamprey homeobox gene (Carr et al, 1998). We have used a 380-kb human YAC construct containing the PPT gene, tagged with the LacZ gene, to determine whether the promoter of the human PPTA gene could drive relevant expression of a marker gene within the mouse.…”
Section: The Transcriptional Mechanisms Governing the Tissue-specificmentioning
confidence: 99%
“…The β subunits of LH and FSH appear to be rate limiting in the formation of these heterodimeric hormones and confer individual hormone specificity. [426][427][428][429][430][431][432] This includes a rather complex analysis of the contributions of combinations of cis regulatory elements in a so-called combinatorial code that control cell-specific regulation. A great deal of research has focused on the cell type-specific regulation of the gonadotropin subunit gene promoters due to their central importance to the regulation of gonadal function and fertility.…”
Section: Regulation Of the Glycoprotein Hormone α Subunit Gene Promotermentioning
confidence: 99%